Current Intake and Infection Status were not Good Predictive Factors of Stunting among Children Aged 6-59 Months in Babakan Madang Sub-District, Bogor District, West Java, Indonesia - Ruth Desinta Purnamasari; Ratu Ayu Dewi Sartika; Trini Sudarti (Indonesian Journal of Public Health Nutrition, 2022)
AbstractThis study aims to discover the prevalence of stunting and determine the associations between the history of pulmonary tuberculosis disease with the prevalence of stunting among children under five years of age (6-59 months) in Babakan Madang Sub-District, Bogor District 2019. This study uses a cross-sectional design with a quantitative approach. The sample in this research was 194 children under five obtained by cluster sampling. Data collection was conducted through May 2019. The data collection process includes anthropometric measurements using calibrated microtoise and digital length board, dietary assessment using 1 x 24-h food recall, and a self-administered questionnaire. Data analyses were performed using the chi-square test and independent t-test. The result of this study shows that 35.6% of children under five are being stunted (HAZ ≤ -2.00). The risk factor with a significant correlation with stunting is history of pulmonary tuberculosis disease (p-value 0.044), although careful interpretation is needed in this result due to the limited number of observed cases. However, this study recommends pulmonary tuberculosis disease prevention and improve nutritional education. Keywords: stunting, children under-five, pulmonary tuberculosis disease AbstrakPenelitian ini bertujuan untuk mengetahui besaran prevalensi stunting dan membuktikan hubungan antara riwayat penyakit TB paru serta faktor lainnya dengan kejadian stunting pada balita umur 6-59 bulan di Kecamatan Babakan Madang Kabupaten Bogor Tahun 2019. Penelitian ini menggunakan desain studi cross-sectional dengan pendekatan kuantitatif. Sampel pada penelitian ini berjumlah 194 balita yang didapat dengan cara cluster sampling. Pengambilan data dilakukan selama bulan Mei 2019. Proses pengambilan data meliputi pengukuran antropometri menggunakan microtoise dan digital length board yang telah divalidasi, wawancara food recall 1x 24 jam, dan pengisian kuesioner. Analisis data dilakukan dengan uji chi-square dan independent-t.  Hasil penelitian ini menunjukkan terdapat 35,6% balita stunting (Z-score PB/U atau TB/U ≤ -2,00). Faktor risiko yang memiliki hubungan signifikan dengan kejadian stunting adalah riwayat penyakit TB paru, meskipun hasil ini memerlukan kehati-hatian dalam interpretasi mengingat sangat terbatasnya jumlah kasus TB paru yang diobservasi. Meskipun demikian, studi ini merekomendasikan upaya pencegahan terhadap penyakit TB paru dan peningkatan edukasi gizi. Kata kunci:  stunting, balita, riwayat TB paru